Modelling the relationship between value managementâs activities and critical success factors for sustainable buildings - Farouk Kineber, A. (Emerald Group Holdings Ltd., 2021)
Purpose: The purpose of this paper is to assess the influence of value management (VM) critical success factors (CSFs) on the implementation of VM activities in building projects with a view to promoting sustainability of construction industry in Egypt. Design/methodology/approach: The VM CSFs and implementation activities were recognized from earlier studies; questionnaire survey was conducted to collect data from relevant stakeholders, and the collected data was subjected to exploratory factor analysis. Consequently, the influence of VM CSFs on VM implementation was generated via partial least square structural equation modelling. In addition, through relative importance ranking analysis, the significance VM CSFs were examined. Findings: The findings from the proposed model revealed a strong relationship between VM implementation activities and its CSFs; the relationship is at a moderate level with an effect of 22.0. This indicates that, VM CSFs would be useful to implement VM in the Egyptian building industry. Research limitations/implications: Although these studies have been confined to Egyptâs VM studies; they may apply to other developing countries that have not carried out these studies. It is therefore vital, in those countries where the exercise has been entirely undertaken, to analyze the various measures to promote the application of the method. Practical implications: This research would be of benefit to stakeholders in building industries to be aware of VM phases and its CSFs that demand utmost consideration. Also, the identified CSFs are expected to enhance the success and value of building projects by adopting VM. Originality/value: The novelty of this research work will be a benchmark or board for decision-makers to eliminate the unwanted cost and enhance quality by adopting VM in Egyptâs building projects to achieve their sustainable projects. Â© 2021, Emerald Publishing Limited.